Quantify the contribution of personality traits according to the risky cognitive method versus caution in performing the skills of rolling up and landing a human wheel on the balance model device in your artistic gym for female students. - Jabbar Mahmood, Sanarya; Naeem Mohsen, Basma; Adnan Abaaab, Hanan (International Journal of Psychosocial Rehabilitation, 2020)
The study of personality and knowledge of its features is the main source of knowledge of the manifestations of human behavior because the subject of personality is an important topic that the psychology touched on to study so far, and the personality is distinguished from other subjects of psychology by emphasizing the complex organization within the individual that general psychology addresses individual psychological functions such as perception, learning, motivation, and emotion. The subject of individual differences between students helps to know the personality traits and predict what will be the behavior of the student in the face of the complex consent in his life and knowing the cognitive methods characteristics of educated individuals is a contributing factor in determining the appropriate educational method for them in dealing with the information and difficulties that they may face during the learning process and the skills of the rise rolling and landing human wheel on the balance model of skills that are difficult for the student to perform with high mastery and that this difficulty is the result of Performance thinking disorders due to individual differences in personality traits and cognitive methods possessed by educated individuals. And in that came the objectives of the research, and as it comes: 1. Learn about the distinctive cognitive method of the research sample (risk calculation) 2. Identify personality traits according to people with a cognitive approach torisk versus caution 3. Recognize the performance of my skills to roll and land a human wheel on acasual device according to those with a cognitive approach: risk versus caution 4- Identify the relationship between personality traits and perform the skills ofrolling up and landing a human wheel on a balance model device according to those with a cognitive approach risk versus caution 5: To identify the contribution ratio of personality traits and the performance of the skills of the rolling up and landing human wheel on the balance model device according to those with a cognitive approach: risk versus caution.